At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's solve the given equation step-by-step to determine which expression is equivalent to [tex]\( 8(2x - 5) - 4(3x - 7) = 7 \)[/tex].
First, we need to distribute the numbers outside the parentheses through each term inside the parentheses.
### Step 1: Distribute the 8 in [tex]\( 8(2x - 5) \)[/tex]
[tex]\[ 8(2x - 5) = 8 \cdot 2x - 8 \cdot 5 = 16x - 40 \][/tex]
### Step 2: Distribute the -4 in [tex]\( -4(3x - 7) \)[/tex]
[tex]\[ -4(3x - 7) = -4 \cdot 3x + 4 \cdot 7 = -12x + 28 \][/tex]
### Step 3: Combine the results from both distributions
[tex]\[ 8(2x - 5) - 4(3x - 7) = 16x - 40 - 12x + 28 \][/tex]
### Step 4: Simplify the combined expression
Combine like terms:
[tex]\[ (16x - 12x) + (-40 + 28) = 4x - 12 \][/tex]
So, the simplified form of the left-hand side of the equation is [tex]\( 4x - 12 \)[/tex]. Setting this equal to the right-hand side, we get:
[tex]\[ 4x - 12 = 7 \][/tex]
### Conclusion
Given these steps, let's see which of the provided options matches the equivalent expression:
1. [tex]\( 16x - 40 - 12x + 28 = 7 \)[/tex]
2. [tex]\( 16x - 5 - 12x - 7 = 7 \)[/tex]
3. [tex]\( 16x - 40 - 12x - 28 = 7 \)[/tex]
4. [tex]\( 16x - 5 + 12 - 7 = 7 \)[/tex]
From our steps, the correct equivalent expression is:
[tex]\[ 16x - 40 - 12x + 28 = 7 \][/tex]
Hence, the equivalent expression to [tex]\( 8(2x - 5) - 4(3x - 7) = 7 \)[/tex] is:
[tex]\[ 16x - 40 - 12x + 28 = 7 \][/tex]
First, we need to distribute the numbers outside the parentheses through each term inside the parentheses.
### Step 1: Distribute the 8 in [tex]\( 8(2x - 5) \)[/tex]
[tex]\[ 8(2x - 5) = 8 \cdot 2x - 8 \cdot 5 = 16x - 40 \][/tex]
### Step 2: Distribute the -4 in [tex]\( -4(3x - 7) \)[/tex]
[tex]\[ -4(3x - 7) = -4 \cdot 3x + 4 \cdot 7 = -12x + 28 \][/tex]
### Step 3: Combine the results from both distributions
[tex]\[ 8(2x - 5) - 4(3x - 7) = 16x - 40 - 12x + 28 \][/tex]
### Step 4: Simplify the combined expression
Combine like terms:
[tex]\[ (16x - 12x) + (-40 + 28) = 4x - 12 \][/tex]
So, the simplified form of the left-hand side of the equation is [tex]\( 4x - 12 \)[/tex]. Setting this equal to the right-hand side, we get:
[tex]\[ 4x - 12 = 7 \][/tex]
### Conclusion
Given these steps, let's see which of the provided options matches the equivalent expression:
1. [tex]\( 16x - 40 - 12x + 28 = 7 \)[/tex]
2. [tex]\( 16x - 5 - 12x - 7 = 7 \)[/tex]
3. [tex]\( 16x - 40 - 12x - 28 = 7 \)[/tex]
4. [tex]\( 16x - 5 + 12 - 7 = 7 \)[/tex]
From our steps, the correct equivalent expression is:
[tex]\[ 16x - 40 - 12x + 28 = 7 \][/tex]
Hence, the equivalent expression to [tex]\( 8(2x - 5) - 4(3x - 7) = 7 \)[/tex] is:
[tex]\[ 16x - 40 - 12x + 28 = 7 \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.